Transitional cell carcinoma of endometrium: a case report of rare pure form - Cuccia, Francesco; Mortellaro, Gianluca; Spera, Antonio; Evangelista, Giovanna; Lo Casto, Antonio; Ferrera, Giuseppe (Journal of Contemporary Brachytherapy, 2018)
Transitional cell carcinoma is a very rare histological subtype of endometrial cancer, with only 18 cases described in literature. Ovary represents the most common site where it accounts for 2% of all ovarian cancers. Due to the rarity of this disease, current management is controversial and includes various approaches, mostly described in the adjuvant setting, both radiotherapy and chemotherapy alone or in combination. Here, we report a case of a 65-year-old patient who underwent adjuvant vaginal brachytherapy for an endometrial transitional cell carcinoma. The patient was treated with radical total abdominal hysterectomy and bilateral salpingo-oophorectomy (TAH-BSO), without lymph-node sampling, and adjuvant endocavitary brachytherapy delivering 30 Gy in 5 fractions in consecutive days. Treatment tolerance was excellent, with only G1 genitourinary acute toxicity and no other adverse events reported. In this experience, the choice of brachytherapy alone resulted in excellent local control outcomes. However, the patient developed a distant recurrence after 43 months and chemotherapy was applied. More research is required to determine the most effective treatment for this rare histological subtype, and in particular, the role of chemotherapy and radiotherapy combinations.